The Theory of Forms Without Substance a Romanian Legal Transplant Theory Ahead of Its Time - Roghină , Răzvan Cosmin (Journal of Legal Studies, 2020)
Comparative law and legal history show us that law is dynamic, always in continuous development, change, or mutation. This dynamic dimension has become a central concern for the comparative law scholars. The circulation of legal models in the world (e.g. legal transplant, legal transfer, legal borrowing, legal migration) is an evergreen issue. This phenomenon has provoked numerous doctrinal disputes, which have been encapsulated in complex theories on its possibilities and impossibilities. In the present article, we will not explore the many modern theories regarding legal transplantation (or under other metaphors). Instead, we will go back in time, in the second half of the nineteenth century, to explore an interesting Romanian theory that seems to have anticipated a series of modern ideas regarding the purpose, possibilities, and impossibilities of the circulation of legal models in the world. Following this approach, the main conclusion will be resumed to the idea that the Romanian theory of forms without substance can be integrated within the modern theories of legal transplant.